MULTILINGUAL THEMATIC PICTURE DICTIONARY: ASSISTING YOUNG LEARNERS’ LITERACY - Wulandari, Putu Ratih; Ratminingsih, Ni Made; Budasi, I Gede (Universitas Pendidikan Ganesha, 2021)
This study aimed at developing a media, named a multilingual thematic picture dictionary to support the development of fourth grade elementary school students’ literacy. This study applied Design and Development research with Analysis, Design, Development, and Evaluation model proposed by Richey and Klein (2007). The subjects of the research were the fourth grade elementary school students who studied in rural and urban area. The data in this study were obtained from observation, interview, questionnaire, document analysis, content validity judgment, and quality judgment. The data obtained were collected by using four instruments, namely; observation sheet, interview guide, questionnaire, and expert judgment sheet. The data were analyzed qualitatively and quantitatively. The results showed that the multilingual thematic picture dictionary contents were relevant to the criteria of a good multilingual thematic picture dictionary and was categorized as an excellent category. Keywords: literacy, young learner, dictionary